Physico-chemical treatment of marble processing wastewater and the recycling of its sludge - Arslan, EI; Aslan, S; Ipek, U; Altun, S; Yazicioglu, S (Sage Publications Ltd, 2005)
In the first part of this study, the treatability of marble processing wastewater by the coagulation-flocculation process was investigated. Optimum coagulant-flocculant doses for turbidity removal in wastewater from the Cutting, faience and equalization processes were determined as 500, 200 and 500 ppm of Al-2(SO4)(3); 300, 500 and 300 ppm of FeCl3 and 600, 400 and 200 ppm of Agrofloc 100 (AGRON Water Treatment Technologies and Chemical Marketing Industry and Trade Limited Company, Izmir, Turkey), respectively. It was found that the removal of total solids from cutting and equalization process wastewaters was highest for the 100 ppm dosage of all chemicals used. The amount of total solids removed from faience process wastewater by Agrofloc 100 was higher than that removed by the other chemicals used. The removals of suspended solids from cutting, faience and equalization process wastewaters were similar to each other for each of the chemicals. The pH values after treatment by Agrofloc 100 were higher than the values determined after treatment by other chemicals for all process wastewater. Electrical conductivity values, however, were lower for Agrofloc 100 than for the others. Settled sludge volume experiments showed that settled sludge volumes decreased with time. The results of the quiescent settling experiment showed that the settling type could be termed flocculent settling. In the second part of the study, the usage of waste sludge from marble processing as an additive material in cement was investigated. The waste sludge originated from the wastewaters of different steps of the marble processing plant. Waste sludge was replaced with cement at various percentages by weight to prepare the mixtures of mortar. The specimens poured into the moulds were held for 24 11, removed from the moulds and held again for 28 days in lime-saturated water at 23 degrees C. Compressive and flexural strengths were evaluated with respect to percentages of waste sludge replaced with cement. The maximum compressive and flexural strengths were observed for specimens containing a 6% waste sludge when compared with control and it was also found that waste Sludge up to 9% could effectively be used as an additive material in cement.
Keywords: marble processing; wastewater; coagulation-flocculation; physico-chemical treatment; sludge; recycling; wmr 898-3